Posebnosti zlomov obraznega skeleta pri starostnikih - Žerdoner, Danijel (Zdravniški vestnik, 2006)
Background Due to anatomic changes of lower jaw and life habits of the population over 60 yeas of age, etiology and therapy of mandible fractures essentially change. In most cases, treatment of lower jaw fractures is operative. Longer osteosynthetic plates are used because of insufficient bloodsupply and osteoporosis. Plate location varies according to atrophy and therefore often differs from basic principles of mandible osteosynthesis. Conclusions The author explains the specific etiology of facial skeleton fractures, their diagnostic, and particularities of osteosynthesis, focusing primarily on mandible fractures.
Keywords: Aged; čeljusti; Diagnosis; diagnostika; etiologija; Etiology; Facial Bones; Injuries; Ličnica, zlomi; Maksila, zlomi; Mandibular Fractures; Mandibularni zlomi; Maxillary Fractures; Obrazne kosti; Starostniki; Therapy; zdravljenje; zlomi; Zygomatic Fractures